1997
DOI: 10.1002/anie.199709551
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring In Situ Growth and Dissolution of Molecular Crystals: Towards Determination of the Growth Units

Abstract: We are grateful to Ada Yonath and her group of the Max-Planck-Insitut fur strukturelle Molekularbiologie, Hamburg for use of laboratory facilities and to the staff of HASYLAB for assistance. We thank Meir Lahav, Isabelle Weissbuch, and Ivan Kuzmenko for discussions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
98
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(103 citation statements)
references
References 27 publications
5
98
0
Order By: Relevance
“…In the 1990s, evidence argued in favor of dimers in glycine solution. [64][65][66][67][68][69][70] However, Yu et al have recently carried out freezing point depression and diffusion measurements of supersaturated aqueous solutions of glycine, and both were consistent with the fact that the solutions are mainly (but not exclusively) monomeric glycine. 63 Moreover, the fact that the diffusion of glycine does not slow as the solution ages contradicts previous models for the formation of dimers.…”
Section: The Crucial Role Of Nucleationmentioning
confidence: 89%
“…In the 1990s, evidence argued in favor of dimers in glycine solution. [64][65][66][67][68][69][70] However, Yu et al have recently carried out freezing point depression and diffusion measurements of supersaturated aqueous solutions of glycine, and both were consistent with the fact that the solutions are mainly (but not exclusively) monomeric glycine. 63 Moreover, the fact that the diffusion of glycine does not slow as the solution ages contradicts previous models for the formation of dimers.…”
Section: The Crucial Role Of Nucleationmentioning
confidence: 89%
“…Note that this methodology is only a metaphor to quantify growth rates and may not reflect upon the actual physical processes involved during crystal growth. For instance, in a-glycine, crystal growth proceeds by the advancement of molecular steps on the (0 1 0) surface according to the ''spiral growth'' mechanism [42,46]. Impurity molecules that are adsorbed on the surface can provide a modified surface energy for the integration of solute molecules, and prevent the progress of kink sites along the step.…”
Section: Article In Pressmentioning
confidence: 99%
“…Solution chemistry of glycine has been also extensively studied (21,37,38). Based on observations by atomic force microscopy and grazing incidence X-Ray diffraction (15,39), it is suggested that glycine molecules in neutral aqueous solutions behave primarily as hydrogenbonded dimers resulting in a crystal structure where the dimer motif is retained. Note that the speculation, mainly based on the measurement of the nucleation process at the crystalliquid interface, is recently questioned (40).…”
Section: Introductionmentioning
confidence: 99%